Analysis of the relationship between upper body speed capacity and lower body strength of elite handball players specialized in winger position - Mihaila, I.; Gavriloaia, R.-A.; Stancu, M.; Mihai, I.; Manole, C.; Acsinte, A.; Popescu, D.-C. (Pedagogy of Physical Culture and Sports, 2024)
Background and Study Aim. The physical demands of the winger position in elite handball require a unique combination of upper body speed and lower body strength. Therefore, identifying the optimal relationship between these two physical characteristics could improve performance for players in this role. This study aims to analyze the relationship between upper body speed capacity and lower body strength in elite handball players specializing in the winger position. Material and Methods. The study included 16 elite handball players specializing in the winger position from various teams in the National Handball League (Liga Zimbrilor). Four of these players were members of the Dinamo Bucharest team. Tests for evaluating the explosive strength of the lower limbs included the Squat Jump (SJ), Counter Movement Jump (CMJ), Counter Movement Jump with Free Arms (CMJb), and the maximum strength test (1RM) in squats. Specific technical training tests included triangular movement, a 30-meter sprint, and long-distance handball throws, focusing on speed and execution technique. Data analysis was conducted using KyPlot 6.0 software. Statistical indicators included median, standard deviation, coefficient of variation, and non-parametric Spearman correlation tests. Statistical significance was set at p < 0.05. Results. The results show no statistically significant differences in lower limb strength between high-performance handball players (HPHP) and those specialized in the winger position (PSW) across various jump and squat tests (p > 0.05). The Countermovement Jump (CMJ) test approached statistical significance (p = 0.084), while the CMJ with free arms (CMJb) and squat strength test did not show significant differences (p = 0.231 and p = 0.789, respectively). In the specific fitness tests, no significant differences were observed in the Triangle Movement test (p = 0.826), the 30-meter sprint (p = 0.404), or the handball throw test (p = 0.147). Correlation analysis indicated that squats and CMJb had positive correlations with improved performance in speed and distance tests, while CMJ showed a negative correlation with technical performance in agility tests. Conclusions. The findings suggest that lower limb strength and technical fitness are similar between elite handball players, regardless of specialization. This supports a unified training approach across player roles. However, targeted exercises like squats and CMJb may enhance specific performance aspects. These exercises improve dynamic strength and stability, which can benefit wingers' technical execution and speed.